Preparation method of continuous directional sequencing ZIF-L membrane for alcohol-water separation
By incorporating ZIF-L material into the sodium alginate membrane and preparing the ZIF-L layer with continuous orientation sorting, the problems of poor water stability and limited mechanical strength of the sodium alginate membrane in high humidity environment are solved, and the alcohol-water separation membrane is realized High performance and long-term stable operation.
Patent Information
- Application Number
- CN202411588281.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing sodium alginate membrane has poor water stability, limited mechanical strength and limited selectivity in high humidity environments, making it difficult to meet the high performance requirements of alcohol-water separation.
The ZIF-L layer was prepared by incorporating ZIF-L material into the sodium alginate membrane and using continuous orientation sorting method to form a high-performance alcohol-water separation membrane. The method includes the synthesis of the two-dimensional leaf material ZIF-L and the preparation of the continuous directional sorting ZIF-L layer, combined with the modification process of sodium alginate, to prepare a membrane with high permeability flux and excellent separation factors.
It improves the stability and separation performance of the membrane, enhances the purification effect of alcohol and water separation, and ensures the long-term stable operation of the membrane.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a high-performance membrane for alcohol-water separation, belonging to the technical field of separation membrane preparation. The modified membrane has high pure water flux and good ethanol separation effect, and is suitable for fields such as alcohol-water separation. Background Art
[0002] Pervaporation membrane technology is an advanced membrane separation technology that uses specially designed polymer membranes to achieve efficient separation of components in liquid mixtures. This technology is based on the principle of selective permeation and vaporization of the membrane and is an important development in the field of membrane science from the late 20th century to the early 21st century. Pervaporation membrane technology is valued for its simple operation, strong adaptability, low energy consumption, high separation efficiency and environmental friendliness. It can achieve molecular-level separation and is not limited by traditional gas-liquid equilibrium. It is particularly suitable for processing systems that are costly or inefficient to use conventional separation methods (such as distillation), such as separating azeotropes, near-boiling substances and heat-sensitive substances.
[0003] As a natural polysaccharide, sodium alginate has shown unique advantages and characteristics in the field of pervaporation membranes. Compared with some synthetic polymers, sodium alginate has relatively low cost and wide sources; sodium alginate is easy to shape and can be prepared into membranes through simple processes such as solution casting and coating, which greatly reduces the difficulty of membrane preparation; because sodium alginate contains a large number of hydroxyl and carboxyl groups in its molecular chain, it has strong hydrophilicity, which is conducive to the permeation of water molecules and greatly enhances the permeation flux of the membrane; sodium alginate can form a thermally irreversible gel when encountering specific ions (such as calcium ions). This property allows the pore structure and mechanical strength of the membrane to be regulated through a simple cross-linking reaction during the preparation of the membrane, which plays an important role in improving the separation performance of the membrane.
[0004] However, sodium alginate membrane has strong hydrophilicity and poor water stability. It may absorb water and swell in a high humidity environment, affecting its structural stability and separation performance. In addition, the mechanical strength is limited. Unmodified sodium alginate membrane has low mechanical strength and is easy to break, which limits its application under certain harsh conditions. The selectivity is limited. Although its separation performance can be improved through modification, the selectivity of natural sodium alginate membrane may not be as good as some specially designed synthetic polymer membranes.
[0005] Therefore, in order to improve the performance of the membrane, porous and non-porous fillers need to be incorporated into the polymer matrix to regulate the synergistic effect between the polymer and filler phases. ZIF-L has a zeolite-like topological structure, excellent thermal and chemical stability, permeability and suitable pore size, which is beneficial to promote molecular sieving and improve the stability and separation performance of sodium alginate membranes. However, the ZIF-L materials synthesized in the current experiment have problems such as chaotic growth orientation and interface defects, which reduce the separation performance of the membrane. Subtly interconnected ZIF-L nanosheets without interface defects help to form a continuous permeation path. For example, Chinese invention application 202310934028.1 discloses a method for preparing a polymer-supported vertical metal-organic framework composite membrane, in which although the ZIF-L layer satisfies the directional growth, the vertical ZIF-L has poor screening effect on ethanol and water. ZIF-L has a hexagonal window-like pore size on the horizontally oriented plane and a very small quaternary window ( Figure 5 ), which is between the kinetic diameters of water (2.68 Å) and ethanol (4.5 Å), and is expected to show a significant screening effect on water / ethanol mixtures. Studies have shown that the growth orientation of ZIF-L gradually tends to the vertical direction over time, which is determined by the ratio of crystal length to width. Therefore, it is necessary to artificially control and prepare a horizontally oriented and continuously oriented ZIF-L layer to meet the needs of alcohol-water separation and purification. Summary of the invention
[0006] The purpose of the present invention is to prepare a continuous directional sorted ZIF-L membrane for alcohol-water separation in view of the current situation that the membrane flux and the separation factor cannot be balanced and cannot well meet the membrane separation requirements.
[0007] The method for preparing the hydrophilic modified sodium alginate membrane has the advantages of high flux and good separation factor, and is suitable for membrane separation process, which can ensure excellent separation effect and long-term stable operation. In order to achieve the above purpose, the technical scheme adopted by the present invention is: a method for preparing a continuous directional sorting ZIF-L membrane for alcohol-water separation, and the specific steps are as follows: (1) Synthesis of two-dimensional leaf-like material ZIF-L The substances involved in the synthesis steps of the two-dimensional leaf-like material ZIF-L are composed according to the following mass percentages, and cobalt nitrate hexahydrate accounts for 31-60% of dimethylimidazole. Dissolve the cobalt nitrate hexahydrate and dimethylimidazole in appropriate amounts of water at room temperature, quickly pour the dimethylimidazole solution into the cobalt nitrate hexahydrate, and stir for 2-4 hours. Pour the solution into a centrifuge tube, centrifuge it three times at a frequency of 6000-8000r / 20min, remove the supernatant and wash it with the solution, collect the lower layer of material into a culture dish, and dry it at 60 degrees Celsius for 5-8 hours. Put it into a mortar and grind it into powder to obtain the two-dimensional leaf-like material ZIF-L.
[0008] (2) Preparation of continuous directional ordered ZIF-L layers Preparation of a continuously oriented ZIF-L layer: Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a solution of appropriate concentration, and ultrasonicate it for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane, and place the filtered PAN-based membrane into the same proportion of the original solution used in the previous synthesis of ZIF-L, and grow it at a suitable temperature for 30-60 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8-12 hours.
[0009] (3) Preparation of high-performance membrane for separation of alcohol and water: Take an appropriate amount of sodium alginate and add it to water, with the sodium alginate accounting for 2-3% of the water ratio. Stir for 3-4 hours to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for separation and purification of alcohol and water. The performance can be tested with different concentrations of ethanol later.
[0010] Preferably, the main reactant for synthesizing ZIF-L in step (1) is one of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, or a cobalt-zinc mixed crystal.
[0011] Preferably, the washing solution after centrifugation in step (1) is one of water, ethanol and acetone.
[0012] Preferably, the solvent in which the powder is redissolved in step (2) is one of water, PEI solution, PDA solution and triethylamine solution.
[0013] Preferably, the mass concentration of the solution in which the powder is redissolved in step (2) is 1 wt% to 3 wt%.
[0014] Preferably, in step (2), the temperature at which the membrane is placed in the solution for growth after filtration is 30°C to 50°C.
[0015] The preferred step (3) of preparing the alcohol-water separation high-performance membrane is as follows: the spin coater speed is required to be 1400r~1600r / min.
[0016] The present invention improves the irregular and messy ZIF-L structure prepared in previous experiments, and uses a secondary growth method to prepare a continuously oriented ZIF-L layer. This study uses a PEI solution as an adhesive. By controlling the direction of the deposited seed layer, a micron-sized ZIF-L nanosheet with PEI as an adhesive is deposited, and then a short growth is performed to form a horizontally oriented layer. When the ZIF-L crystal suspension is vacuum filtered, there is a normal force acting on the ZIF-L crystals near the carrier, that is, the resistance under vacuum. The resistance causes the solution to be transferred to the carrier and deposits the ZIF-L crystals on the surface. A large number of ZIF-L particles are well dispersed in the PEI matrix, and PEI can form hydrogen bonds with the ZIF-L crystals and the free hydroxyl groups on the support surface, and can also form Zn-N coordination bonds with the zinc cations on the crystal surface. Therefore, adding PEI to the seed solution is crucial to ensure that the seed crystals are firmly adhered to the support surface, and is the key to ensuring the horizontal growth of the seed crystals. The horizontally oriented ZIF-L layer can effectively fill the gaps between ZIF-L crystals, improve the defects of the ZIF-L-SA membrane caused by the previous blending, and improve the material performance. Beneficial Effects
[0017] The ordered arrangement and regular pore size of ZIF-L provide an ordered water channel for the rapid transmission of water molecules; the nominal diameter of ZIF-L is 3.4 Å, which is between the kinetic diameters of water (2.68 Å) and ethanol (4.5 Å). The appropriate pore size of ZIF-L can produce a sieving effect between the kinetic diameters of water and ethanol. Due to the horizontal directional arrangement of ZIF-L, the intercrystalline gaps of ZIF-L can be effectively filled, the interface defects can be improved, and the separation layer can also produce a good sieving effect, greatly enhancing the separation performance of the membrane; the adhesive used in the process increases the hydrophilicity of the membrane; it forms coordination bonds with the ZIF-L crystals and free hydroxyl groups on the support surface, and also improves the stability of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Figure 10 shows the ZIF-L synthesized in Example 10. Figure 2 Figure 2 shows the ZIF-L synthesized in Example 2. Figure 3 Figure 4 shows the ZIF-L synthesized in Example 4. Figure 4 This is a surface scanning electron microscope image of the pervaporation membrane of Example 10. Figure 5 The horizontal pore structure of ZIF-L DETAILED DESCRIPTION
[0019] The present invention is further described in detail below by specific embodiments. However, those skilled in the art will appreciate that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention.
[0020] The continuous directional ordered ZIF-L membrane prepared by the present invention can be used to separate ethanol and water, so the membrane permeation flux, alcohol-water separation factor and stability performance are three important parameters for evaluating the pervaporation.
[0021] The test conditions of membrane permeation flux and alcohol-water separation factor are as follows: pervaporation device, ethanol concentration of 80-90%, test temperature of 75°C, and test pressure of 300Pa.
[0022] The membrane permeation flux (J) is defined as:
[0023] Where Q represents the total mass of the permeate, g; A represents the effective membrane area, m 2 ; t represents the duration of collection, h.
[0024] The alcohol-water separation coefficient (α) is defined as:
[0025] In the formula, X A and X B Respectively represent the concentration of ethanol and water in the raw material solution, wt%; Y A and Y B Represent the concentrations of ethanol and water in the permeate, wt %, respectively. Example
[0026] (1) Take 0.59 g of Co(NO3)2·6H2O and 1.30 g of dimethylimidazole (Hmim) and dissolve them in 40 mL of water. After stirring and dissolving, pour the cobalt nitrate solution into the dimethylimidazole solution quickly and stir at room temperature for 4 h. Collect the two-dimensional ZIF-L crystals by repeated centrifugation (8000 rpm, 20 min), wash them with deionized water three times, dry them at 60 °C in vacuum and grind them to obtain ZIF-L nanosheets.
[0027] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and dissolve it in water again. Ultrasonicate for a period of time to make it completely dissolved. Use a vacuum filter to filter it onto the PAN-based membrane. Put the filtered PAN-based membrane into the synthetic solution of ZIF-L in the same proportion and grow it in a 30℃ water bath for 30 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0028] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1400r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0029] The ZIF-L layer structure prepared in Example 1 is arranged in a disordered manner. The pervaporation membrane prepared in Example 1 was tested and the membrane permeation flux was 1200 g / m 2 *h, the alcohol-water separation coefficient is 720. Example
[0030] (1) Take 0.59 g of Co(NO3)2·6H2O and 1.30 g of dimethylimidazole (Hmim) and dissolve them in 40 mL of water. After stirring and dissolving, pour the cobalt nitrate solution into the dimethylimidazole solution quickly and stir at room temperature for 4 h. Collect the two-dimensional ZIF-L crystals by repeated centrifugation (8000 rpm, 20 min), wash them with deionized water three times, dry them at 60 °C in vacuum and grind them to obtain ZIF-L nanosheets.
[0031] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 1wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 30℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0032] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0033] The ZIF-L layer leaves prepared in Example 2 are arranged relatively horizontally, but are still partially disordered. The pervaporation membrane prepared in Example 2 was tested, and the membrane permeation flux was 1300 g / m 2 *h, the alcohol-water separation coefficient is 1100. Example
[0034] (1) Take 0.78g of Co(NO3)2·6H2O and 1.30g of dimethylimidazole (Hmim) and dissolve them in 40mL of water respectively. After stirring and dissolving, the cobalt nitrate solution is quickly poured into the dimethylimidazole solution and stirred at room temperature for 4h. The two-dimensional ZIF-L crystals are collected by repeated centrifugation (7000 rpm, 15 min), washed with deionized water three times, dried at 60℃ in vacuum and ground to obtain ZIF-L nanosheets.
[0035] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 1wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 30℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0036] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0037] The ZIF-L prepared in Example 3 has a more complete morphology and a better dispersion effect. The pervaporation membrane prepared in Example 3 was tested and the membrane permeation flux was 1600 g / m 2 *h, the alcohol-water separation coefficient is 1300. Example
[0038] (1) Take 0.9 g of Co(NO3)2·6H2O and 1.30 g of dimethylimidazole (Hmim) and dissolve them in 40 mL of water. After stirring and dissolving, pour the cobalt nitrate solution into the dimethylimidazole solution quickly and stir at room temperature for 4 h. Collect the two-dimensional ZIF-L crystals by repeated centrifugation (7000 rpm, 15 min), wash them with deionized water three times, dry them at 60 °C in vacuum and grind them to obtain ZIF-L nanosheets.
[0039] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 1wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it at 30°C for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0040] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0041] The ZIF-L layer blades prepared in Example 4 were severely stacked. The pervaporation membrane prepared in Example 4 was tested and the membrane permeation flux was 1500 g / m 2 *h, the alcohol-water separation coefficient is 1000. Example
[0042] (1) Take 0.78g of Co(NO3)2·6H2O and 1.30g of dimethylimidazole (Hmim) and dissolve them in 40mL of water respectively. After stirring and dissolving, the cobalt nitrate solution is quickly poured into the dimethylimidazole solution and stirred at room temperature for 4h. The two-dimensional ZIF-L crystals are collected by repeated centrifugation (7000 rpm, 15 min), washed with deionized water three times, dried at 60℃ in vacuum and ground to obtain ZIF-L nanosheets.
[0043] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 2wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 30℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0044] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0045] The horizontal orientation degree of the ZIF-L layer prepared in Example 5 is 80%. The pervaporation membrane prepared in Example 5 is tested, and the membrane permeation flux is 1600 g / m 2 *h, alcohol-water separation coefficient is 1500. Example
[0046] (1) Take 0.78g of Co(NO3)2·6H2O and 1.30g of dimethylimidazole (Hmim) and dissolve them in 40mL of water respectively. After stirring and dissolving, the cobalt nitrate solution is quickly poured into the dimethylimidazole solution and stirred at room temperature for 4h. The two-dimensional ZIF-L crystals are collected by repeated centrifugation (7000 rpm, 15 min), washed with deionized water three times, dried at 60℃ in vacuum and ground to obtain ZIF-L nanosheets.
[0047] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 2wt% PDA solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 30℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0048] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0049] The horizontal orientation degree of the ZIF-L layer prepared in Example 6 is 60%, but there is a certain amount of stacking between the blades. The pervaporation membrane prepared in Example 6 was tested, and the membrane permeation flux was 1800 g / m 2 *h, the alcohol-water separation coefficient is 1200. Example
[0050] (1) Take 0.78g of Co(NO3)2·6H2O and 1.30g of dimethylimidazole (Hmim) and dissolve them in 40mL of water respectively. After stirring and dissolving, the cobalt nitrate solution is quickly poured into the dimethylimidazole solution and stirred at room temperature for 4h. The two-dimensional ZIF-L crystals are collected by repeated centrifugation (7000 rpm, 15 min), washed with deionized water three times, dried at 60℃ in vacuum and ground to obtain ZIF-L nanosheets.
[0051] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 2wt% triethylamine solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 30℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0052] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0053] The horizontal orientation degree of the ZIF-L layer prepared in Example 7 was 50%, and the blades were seriously stacked. The pervaporation membrane prepared in Example 7 was tested, and the membrane permeation flux was 1400 g / m 2 *h, the alcohol-water separation coefficient is 1300. Example
[0054] (1) Take 0.78g of Zn(NO3)2·6H2O and 1.30g of dimethylimidazole (Hmim) and dissolve them in 40mL of water respectively. After stirring and dissolving, the cobalt nitrate solution is quickly poured into the dimethylimidazole solution and stirred at room temperature for 4h. The two-dimensional ZIF-L crystals are collected by repeated centrifugation (7000 rpm, 15 min), washed with deionized water three times, dried at 60℃ in vacuum and ground to obtain ZIF-L nanosheets.
[0055] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 2wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 30℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0056] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0057] The ZIF-L prepared in Example 8 is compared with the ZIF-L prepared by Co 2+ The central ion has an aspect ratio that is more like a blade type, and the material is more complete, but there are still 10% defects. The pervaporation membrane prepared in Example 8 was tested, and the membrane permeation flux was 1900 g / m 2 *h, the alcohol-water separation coefficient is 1600. Example
[0058] (1) Take 0.59 g of Zn(NO3)2·6H2O and 1.30 g of dimethylimidazole (Hmim) and dissolve them in 40 mL of water. After stirring and dissolving, pour the cobalt nitrate solution into the dimethylimidazole solution quickly and stir at room temperature for 4 h. Collect the two-dimensional ZIF-L crystals by repeated centrifugation (7000 rpm, 15 min), wash them with deionized water three times, dry them at 60 °C in vacuum and grind them to obtain ZIF-L nanosheets.
[0059] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 2wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 30℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0060] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0061] The ZIF-L material structure prepared in Example 9 has 30% defective parts, and the stacking of the prepared ZIF-L layers is relatively serious. The pervaporation membrane prepared in Example 9 was tested, and the membrane permeation flux was 1600 g / m 2 *h, the alcohol-water separation coefficient is 1300.
[0062] Embodiment 10: (1) Take 0.5g Zn(NO3)2·6H2O, 0.3g Co(NO3)2·6H2O and 1.30g dimethylimidazole (Hmim) and dissolve them in 40mL water. After stirring and dissolving, pour the cobalt nitrate solution into the dimethylimidazole solution quickly and stir at room temperature for 4h. Collect the two-dimensional ZIF-L crystals by repeated centrifugation (7000 rpm, 15 min), wash them with deionized water three times, dry them at 60℃ in vacuum and grind them to obtain ZIF-L nanosheets.
[0063] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 2wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 40℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0064] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0065] The morphology and structure of the ZIF-L material prepared in Example 10 is basically a full blade structure without obvious defects. The horizontal orientation degree of the prepared ZIF-L layer is 95% and the dispersion is good. The pervaporation membrane prepared in Example 10 is tested, and the membrane permeation flux is 2100 g / m 2 *h, the alcohol-water separation coefficient is 1800.
[0066] Embodiment 11: (1) Take 0.3g of Zn(NO3)2·6H2O, 0.5g of Co(NO3)2·6H2O and 1.30g of dimethylimidazole (Hmim) and dissolve them in 40mL of water. After stirring and dissolving, pour the cobalt nitrate solution into the dimethylimidazole solution quickly and stir at room temperature for 4h. Collect the two-dimensional ZIF-L crystals by repeated centrifugation (7000 rpm, 15 min), wash them with deionized water three times, dry them at 60℃ in vacuum and grind them to obtain ZIF-L nanosheets.
[0067] (2) Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a 2wt% PEI solution. Ultrasonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane. Place the filtered PAN-based membrane into the same proportion of ZIF-L synthesis solution and grow it in a 40℃ water bath for 40 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8 hours.
[0068] (3) Take 1.25g of sodium alginate and add it to 48.75g of water. Stir for 4h to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer, and then put it into a spin coater for spin coating at a speed of 1600r / min. The casting solution spreads on the silicon wafer to form a thin layer. Treat the bubbles on the surface of the thin layer to make it defect-free, and place the spin-coated membrane on an air drying rack to dry naturally, so as to obtain a high-performance membrane for alcohol-water separation and purification.
[0069] The ZIF-L material structure prepared in Example 11 still has certain defects, and there are some rod-like structures. The pervaporation membrane prepared in Example 11 was tested, and the membrane permeation flux was 1800 g / m 2 *h, alcohol-water separation coefficient is 1500.
Claims
1. A method for preparing a continuous directional sorted ZIF-L high-performance membrane for alcohol-water separation, the specific steps of which are as follows: Synthesis of two-dimensional leaf-like material ZIF-L: The substances involved in the synthesis steps of the two-dimensional leaf-like material ZIF-L are composed according to the following mass percentages, and cobalt nitrate hexahydrate accounts for 31-69% of dimethylimidazole. Dissolve cobalt nitrate hexahydrate and dimethylimidazole in appropriate amounts of water at room temperature, quickly pour the dimethylimidazole solution into the cobalt nitrate hexahydrate, and stir for 2-4 hours. Pour the solution into a centrifuge tube, centrifuge it three times at a frequency of 6000-8000r / 20min, remove the supernatant and wash it with the solution, collect the lower layer of material into a culture dish, and dry it at 60 degrees Celsius for 5-8 hours. Put it into a mortar and grind it into powder to obtain the two-dimensional leaf-like material ZIF-L; Preparation of a continuously oriented ZIF-L layer: Take an appropriate amount of the ZIF-L powder prepared in (1) and redissolve it in a solution of appropriate concentration, and sonicate for a period of time to completely dissolve it. Use a vacuum filter to filter it onto a PAN-based membrane, and place the filtered PAN-based membrane into the same proportion of the original solution used in the previous synthesis of ZIF-L, and grow it at an appropriate temperature for 30-60 minutes. Take it out, rinse it with deionized water, and dry it at room temperature for 8-12 hours; Preparation of high-performance membrane for separation of alcohol and water: Take an appropriate amount of sodium alginate and add it to water, with the sodium alginate accounting for 2-3% of the water ratio, stir for 3-4 hours to obtain a transparent casting solution, and let it stand to degas. Pour the casting solution on the ZIF-L layer prepared in step (2), spread it into a thin layer and then put it into a spin coater for spin coating. The casting solution is spread on the silicon wafer to form a thin layer. The bubbles on the surface of the thin layer are treated to make it defect-free, and the spin-coated membrane is placed on an air drying rack to dry naturally, so that a high-performance membrane for separation and purification of alcohol and water is obtained, and the performance can be tested with different concentrations of ethanol later.
2. The preparation method according to claim 1, characterized in that The main reactant for synthesizing ZIF-L in step (1) is one of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, or a cobalt-zinc mixed crystal.
3. The preparation method according to claim 1, characterized in that The washing solution after centrifugation in step (1) is one of water, ethanol and acetone.
4. The preparation method according to claim 1, characterized in that The solvent in which the powder is redissolved in step (2) is water, a PEI solution of appropriate concentration, a PDA solution, or a triethylamine solution.
5. The preparation method according to claim 1, characterized in that The growth temperature in step (2) is 30°C to 50°C.
6. The preparation method according to claim 1, characterized in that Preparation of high-performance membrane for alcohol-water separation in step (3): The spin coater speed is required to be 1400r~1600r / min.
7. The method for preparing a continuous directional sorted ZIF-L high-performance membrane according to any one of claims 1 to 6, wherein the prepared high-performance pervaporation membrane for alcohol-water separation is characterized in that: The pure water flux of the composite membrane is 2100 g·m -2 ·h -1 , the separation factor is 1800, and it has certain stability and anti-pollution properties.
Citation Information
Patent Citations
Preparation method of polymer-supported vertical metal organic framework (MOF) composite membrane
CN116808856A
Cited By
Horizontal orientation ZIF-L composite film and preparation method thereof
CN120393773A
A horizontally oriented zif-l composite membrane and a method of making the same
CN120393773B
C-PEI-ZIF-8 mixed matrix membrane based on reverse filling method as well as preparation method and application of c-PEI-ZIF-8 mixed matrix membrane
CN121490598A
C-peizif-8 hybrid matrix membrane based on reverse filling method, preparation method and application thereof
CN121490598B